2014
DOI: 10.1186/1710-1492-10-57
|View full text |Cite
|
Sign up to set email alerts
|

Two year effects of food allergen immunotherapy on quality of life in caregivers of children with food allergies

Abstract: BackgroundFood allergy (FA) can have serious psychosocial and economic repercussions on food-allergic children and their caregivers and be associated with negative effects on their quality of life. Food allergen immunotherapy (IT) is a promising experimental therapy but can be linked to anxiety. This study investigated the effects of IT on FA-specific health-related quality of life (HRQL) over a 24 month-follow-up in caregivers of children with single and multiple food allergies. We hypothesized that character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Studies in patients and parents have demonstrated a general positive effect of OIT on some aspects of QoL, especially food anxiety and social and dietary limitation but not emotional impact . Certain characteristics seem to be associated with greater improvements in caregiver QoL: in a prospective randomized study, QoL improved more in caregivers of participants older than 10 years or desensitized to more than 4 food allergens than those who were not …”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…Studies in patients and parents have demonstrated a general positive effect of OIT on some aspects of QoL, especially food anxiety and social and dietary limitation but not emotional impact . Certain characteristics seem to be associated with greater improvements in caregiver QoL: in a prospective randomized study, QoL improved more in caregivers of participants older than 10 years or desensitized to more than 4 food allergens than those who were not …”
Section: Results From the Selected Literaturementioning
confidence: 99%
“…Also these studies showed that it did improve quality of life for families who have children with food allergy [5].…”
Section: Oral Immunotherapymentioning
confidence: 98%
“…Furthermore, the impact on quality of life needs to be better elucidated . FA is associated with a negative impact on the quality of life of patients and their families . To buy special foods, to limit social encounters, to lose time from work, to change careers, and to visit emergency room have been reported to play a predominant role in the total annual economic burden of FA …”
Section: Issues For Clinical Practicementioning
confidence: 99%
“…On the other side, OIT, though logistically demanding and with side effects, might lead to significant and long‐term improvements in health‐related quality of life of patients and their caregivers …”
Section: Issues For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation